Stable isotope probing and metagenomics highlight the effect of plants on uncultured phenanthrene-degrading bacterial consortium in polluted soil - Thomas, François (ISME J, 2019)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous soil pollutants. The discovery that plants can stimulate microbial degradation of PAHs has promoted research on rhizoremediation strategies. We combined DNA-SIP with metagenomics to assess the influence of plants on the identity and metabolic functions of active PAH-degrading bacteria in contaminated soil, using phenanthrene (PHE) as a model hydrocarbon. (13)C-PHE dissipation was 2.5-fold lower in ryegrass-planted conditions than in bare soil. Metabarcoding of 16S rDNA revealed significantly enriched OTUs in (13)C-SIP incubations compared to (12)C-controls, namely 130 OTUs from bare soil and 73 OTUs from planted soil. Active PHE-degraders were taxonomically diverse (Proteobacteria, Actinobacteria and Firmicutes), with Sphingomonas and Sphingobium dominating in bare and planted soil, respectively. Plant root exudates favored the development of PHE-degraders having specific functional traits at the genome level. Indeed, metagenomes of (13)C-enriched DNA fractions contained more genes involved in aromatic compound metabolism in bare soil, whereas carbohydrate catabolism genes were more abundant in planted soil. Functional gene annotation allowed reconstruction of complete pathways with several routes for PHE catabolism. Sphingomonadales were the major taxa performing the first steps of PHE degradation in both conditions, suggesting their critical role to initiate in situ PAH remediation. Active PHE-degraders act in a consortium, whereby complete PHE mineralization is achieved through the combined activity of taxonomically diverse co-occurring bacteria performing successive metabolic steps. Our study reveals hitherto underestimated functional interactions for full microbial detoxification in contaminated soils.